Profitability and Economic Viability of Commercial Dairy farms in Trans-Gangetic Plains of India: Profitability of commercial dairy farms - Arti, AK Chauhan, Anil Kumar Dixit Chandan Kumar Rai and Bitan Mondal (Indian Journal of Dairy Science, 2024)
The profitability of selected commercial dairy farms has been was calculated through estimating cost and returns from commercial dairy farms. The sampled commercial dairy farms were categorized into small, medium and large farms based on herd size. The total cost was worked out to be ₹90.66 lakh, ₹154.96 lakh and ₹254.62 lakh in small, medium and large commercial dairy farms, respectively. The net returns per farm per year were ₹16.10 lakh, ₹52.79 lakh and ₹95.39 lakh in small, medium and large commercial dairy farms, respectively. The net income per income per milch animal per day was ₹66.76, ₹130.00 and ₹139.13 in ascending order of herd size category. The cost of milk production was estimated as ₹31.50, ₹29.10 and ₹26.97 in small, medium and large commercial dairy farms, respectively. The return per litre was ₹6.10, ₹10.57 and ₹11.03 in same order of farm category. Economic viability of dairy farms were measured by liquidity, solvency and profitability ratios. All the ratios were found to be more than standard values shows that all the farms are profitable both in short and long run.